Nasal odorant metabolism: enzymes, activity and function in olfaction. (3rd April 2019) - Heydel, Jean-Marie; Faure, Philippe; Neiers, Fabrice
Abstract: The nasal tissues have the main consecutive roles of moistening and heating the air entering the respiratory tract and detecting odor via the activation of olfactory receptors in the neuro-olfactory epithelium. Initially, nasal toxicology was investigated to better assess the risk of nasal injuries caused by environmental toxicants or their active metabolites. Later, the characterization of the nasal toxicological barrier was a research concern for the purposes of intranasal drug delivery. Both fields allowed for an increase in our knowledge of the nasal xenobiotic-metabolizing enzymes and transporters that are highly expressed in this tissue. In addition to airborne toxicants or drugs, the main substrates for these proteins are natural volatiles known as odorants that emanate from our daily environment (food, perfume, plants, materials, congeners, etc.). Accordingly, another emerging field of interest has been developed that aims to understand the function of odorant-metabolizing enzymes (OMEs) in olfaction. Early in this field of research, OMEs were suspected to participate in the clearance of odorants from the receptor environment to avoid their saturation and thus maintain the sensitivity of neuronal detection. Other roles of OMEs that could significantly modulate olfaction were also considered, such as the involvement of odorant primary metabolites in the olfactory response. By combining enzymatic, physiological and sensory experimental approaches, recent advances have markedly improved our understanding of the contributions of OMEs to the olfactory process. This review combines recent data from the literature regarding nasal OME identification, localization, and activity and highlights the function of OMEs in olfaction.